1989
DOI: 10.1063/1.457121
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic energy dependence of partial cross sections for the collisional ionization of H2O, H2S, O2, and Ar with He(2 3S) metastable atoms

Abstract: The kinetic-energy dependences of partial cross section σ(E) for the collisional ionization of H2O, H2S, O2, and Ar with He(2 3S) metastable atoms are measured in the energy range of 40–300 meV by collision-energy-resolved electron spectroscopy. The σ(E) functions are markedly dependent on the system and, in some cases, on final ionic states because of the anisotropy of incoming interaction potential surfaces or potential surface crossings with other potentials. Negative energy dependences of σ(E) are obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 23 publications
1
87
0
Order By: Relevance
“…[14][15][16][17] The time-of-flight (TOF) method was adapted in our group rather than the velocitycontrolled supersonic jet beam, [18][19][20] since the TOF method has the advantage in measurement of collision-energy/electronenergy-resolved two-dimensional Penning ionization electron spectroscopy (2D-PIES). 21 The 2D spectrum is accumulated as a function of two parameters, kinetic energy (E e ) of ejected electrons and collision energy (E c ) between A* and M. Cuts of the 2D spectrum at selected ionization bands give CEDPICS, while cuts of the 2D spectrum at selected collision energies provide collision-energy-resolved Penning ionization electron spectra (CERPIES).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] The time-of-flight (TOF) method was adapted in our group rather than the velocitycontrolled supersonic jet beam, [18][19][20] since the TOF method has the advantage in measurement of collision-energy/electronenergy-resolved two-dimensional Penning ionization electron spectroscopy (2D-PIES). 21 The 2D spectrum is accumulated as a function of two parameters, kinetic energy (E e ) of ejected electrons and collision energy (E c ) between A* and M. Cuts of the 2D spectrum at selected ionization bands give CEDPICS, while cuts of the 2D spectrum at selected collision energies provide collision-energy-resolved Penning ionization electron spectra (CERPIES).…”
Section: Introductionmentioning
confidence: 99%
“…The velocity distributions of the primary beams were determined by a conventional time-offlight ͑TOF͒ technique. The obtained results are v s ϭ515 and ␣ s ϭ95 for CH 3 Br beam and v s ϭ680 and ␣ s ϭ360 for the Ar͑ 3 P) beam, where all are in units of ms Ϫ1 , where v s and ␣ s are the stream velocity and its width of the velocity distribution, respectively. The rotational temperature is determined to be 50Ϯ5 K.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the electron density distribution of the orbital from where the electron is removed is probed by Penning ionization, and the collision energy dependence of the ionization cross section has been regarded as a good measure to clarify the anisotropy of the intermolecular force. [1][2][3][4][5][6][7][8][9][10] Although studies of the steric effect in Penning ionization have been of much interest, only a few ''direct'' experimental evidences have been reported. For instance, the steric effect in the Ar͑ 3 P͒ϩCH 3 Cl→ArϩCH 3 Cl ϩ ϩe Ϫ reaction was studied in our laboratory by using the electrostatic hexapole method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions of charged particles like electrons, positrons, and ions with water molecule are of fundamental importance in many fields including physics [1][2][3][4], radiobiology, and even medicine [5,6]. Indeed, the living cells being constituted of about 50-80% water in mass, the water molecule represents an ideal surrogate target to investigate the radio-induced ionizing processes in biological matter.…”
Section: Introductionmentioning
confidence: 99%